(untitled) (In situ, 2024)
The bay of Caska is located on the northeastern part of the island of Pag, only 3 kilometers from Novalja in a straight line. The remains of an ancient settlement were found in the bay, at the very edge of the fertile fields of Novalja and Caska, where more intensive activities took place in the period from the 1st century BC to the 3rd century AD. Investigations of the site began in 2003, and from 2009 until today, they have been carried out systematically, with short interruptions, within the CissAntiqua project. In 2023, the research was carried out in the second half of May, at the eastern end of sector 1, in zone D, where the boat Caska 2 from the 1st century AD was investigated during previous campaigns.